Functional Characterization of Rare Variants in OAT1/SLC22A6 and OAT3/SLC22A8 Urate Transporters Identified in a Gout and Hyperuricemia Cohort - Vávra, Jiří; Mančíková, Andrea; Pavelcová, Kateřina; Hasíková, Lenka; Bohatá, Jana; Stibůrková, Blanka (Cells, 2022)
The OAT1 (SLC22A6) and OAT3 (SLC22A8) urate transporters are located on the basolateral membrane of the proximal renal tubules, where they ensure the uptake of uric acid from the urine back into the body. In a cohort of 150 Czech patients with primary hyperuricemia and gout, we examined the coding regions of both genes using PCR amplification and Sanger sequencing. Variants p.P104L (rs11568627) and p.A190T (rs146282438) were identified in the gene for solute carrier family 22 member 6 (SLC22A6) and variants p.R149C (rs45566039), p.V448I (rs11568486) and p.R513Q (rs145474422) in the gene solute carrier family 22 member 8 (SLC22A8). We performed a functional study of these rare non-synonymous variants using the HEK293T cell line. We found that only p.R149C significantly reduced uric acid transport in vitro. Our results could deepen the understanding of uric acid handling in the kidneys and the molecular mechanism of uric acid transport by the OAT family of organic ion transporters.
Keywords: OAT3; Gout; Hyperuricemia; kyselina močová; protein 1 přenášející organické anionty; HEK293 buňky; OAT1; přenašeče organických aniontů nezávislé na sodíku; HEK293 Cells; hyperuricemia; Uric Acid; urate transport; biologický transport; lidé; gout; Humans; dna (nemoc); Organic Anion Transporters, Sodium-Independent; Organic Anion Transport Protein 1; Biological Transport; hyperurikemie